2021
DOI: 10.1002/ejic.202100751
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Macrocyclic and Acyclic Picolinate Derivatives for Chelation of Copper Cations

Abstract: In this work we presented a synthesis and investigation of relative acyclic and macrocyclic polyamines with picolinate pendant arms as potential chelators for copper radiopharmaceuticals. It has been shown that linear chelators lacking bisamide moiety are much more basic and form complexes with higher stability constants compared to macrocyclic ones. Both types of ligands possess many donor sites due to picolinate groups enabling formation of polynuclear complexes in the solution and solid state. According to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…[3][4][5] Recently, a comparative study of macrocyclic and acyclic picolinate derivatives for interaction with copper ions was carried out, and both compounds acted distinctively upon chelation with the metal. 6 Similar changes were observed with protein interaction studies, in which a high-level fold difference in the half-maximal inhibitory concentration (IC 50 ) between linear and cyclic analogues was exhibited. 7,8 These state-of-the-art research outcomes provide hints that molecules act differently towards proteins and metals upon change in their architecture.…”
Section: Introductionsupporting
confidence: 66%
“…[3][4][5] Recently, a comparative study of macrocyclic and acyclic picolinate derivatives for interaction with copper ions was carried out, and both compounds acted distinctively upon chelation with the metal. 6 Similar changes were observed with protein interaction studies, in which a high-level fold difference in the half-maximal inhibitory concentration (IC 50 ) between linear and cyclic analogues was exhibited. 7,8 These state-of-the-art research outcomes provide hints that molecules act differently towards proteins and metals upon change in their architecture.…”
Section: Introductionsupporting
confidence: 66%
“…Moreover, the latter was more stable than a similar copper complex with a tripicolinate derivative of 18-azacrown-6, which released about 20% of the copper within 2 hours and was much more stable than the dipicolinate derivative of 15-azacrown-5 in the same excess of serum. 28 Taking into account a similar "out-cage" coordination with tripicolinate 18-azacrown-6, it can be concluded that coordination 1 (Fig. 7), specifically, in CuBATPic 2− induces the strongest chelation of Cu 2+ .…”
Section: In Vitro Stabilitymentioning
confidence: 87%
“…Such an out-cage coordination has previously been shown for other 18-azacrown-6 derivatives. 26,28 These complexes indicate that, in the case of small cations, the large macrocyclic cavity does not implement a macrocyclic effect, but mainly plays a restricting role in flexible backbones with donor pendant arms.…”
Section: Crystal Structure Of Cu 2 Batpy(clo 4 )mentioning
confidence: 99%
See 1 more Smart Citation
“…Given the growing importance of nuclear medicine and the extending abilities of obtaining medically relevant radiometals, the design of functional polyazamacrocyclic ligands able to coordinate cations with suitable features has been attracting increased attention during the last decade. In the frame of systematic variation and the search for the best matching pairs between medical radiometals and chelators, we have synthesized those substituted with one type of arm and arm-free pyridine bisamide azacrown and benzoazacrown ethers [ 1 , 2 , 3 , 4 , 5 , 6 ]. We have shown that azacrown compounds with acetic arms are effective for binding bismuth [ 4 , 5 ], lead [ 7 ] and zinc [ 8 ] cations, regarding the nuclear medicine application of their radioisotopes.…”
Section: Introductionmentioning
confidence: 99%